2018
DOI: 10.1002/jsfa.9167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fungicides and weather on cyclodepsipeptide‐producing Fusarium spp. and beauvericin and enniatin levels in wheat grains

Abstract: Our study provides new insights into the occurrence of the emerging cyclodepsipeptide mycotoxins in an agro-ecosystem in which fungicides are the main control measure against FHB. It seems that beauvericin and enniatin levels are affected by different parameters and behave differently upon application of fungicides. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…There is a high occurrence of BEA in grains and wheat-based products like pasta, infant formulas, breakfast cereals, and biscuits, with incidences between 40 and 90% (Santini et al, 2012 ; Stanciu et al, 2017 ). In recent years, BEA has frequently been reported in different countries (South Africa, Norway, China, Croatia, Poland, Spain, Morocco…) as contaminants of, especially wheat, rye, oats, barley, and rice (Decleer et al, 2018 ). Seed-borne infection of wheat with F. proliferatum leads to contamination of wheat kernels with BEA (15–55 μg/kg) (Guo et al, 2016 ).…”
Section: Risk Assessment Of Beauvericin In Food and Feedmentioning
confidence: 99%
“…There is a high occurrence of BEA in grains and wheat-based products like pasta, infant formulas, breakfast cereals, and biscuits, with incidences between 40 and 90% (Santini et al, 2012 ; Stanciu et al, 2017 ). In recent years, BEA has frequently been reported in different countries (South Africa, Norway, China, Croatia, Poland, Spain, Morocco…) as contaminants of, especially wheat, rye, oats, barley, and rice (Decleer et al, 2018 ). Seed-borne infection of wheat with F. proliferatum leads to contamination of wheat kernels with BEA (15–55 μg/kg) (Guo et al, 2016 ).…”
Section: Risk Assessment Of Beauvericin In Food and Feedmentioning
confidence: 99%
“…These variations of the species within the FHB complex may have been caused, among other factors, by the application of fungicides usually sprayed to control the disease, 55 possibly increasing the occurrence of less susceptible species in the heads 56 . Our in vitro experiments showed that tebuconazole, metconazole, prothioconazole and prochloraz were highly effective in controlling all four FHB causal agents.…”
Section: Discussionmentioning
confidence: 76%
“…Beauvericin was produced by all investigated fungi, with the most efficient producers being Fusarium strains, such as F. proliferatum (RT6.7, RT 5.4) and F. concentricum (P35). To some extent, all of the studied fungi are known producers of beauvericin [ 42 ], however, it is important to note that each fungal strain possesses unique abilities to produce different amounts of BEA, which can also be affected by the cultivation conditions [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the two phytopathogenic fungal species F. proliferatum and F. oxysporum did not synthesize enniatin analogues, although they have earlier been described as enniatin producers [ 16 , 29 , 42 , 60 ]. This suggests a need for comprehensive reevaluation of cyclodepsipeptide profiles across multiple representatives of known producing taxa, in particular as the production of enniatins may depend on cultivation conditions, storage conditions or the host and the environment from which the fungi were isolated [ 59 ].…”
Section: Resultsmentioning
confidence: 99%